2016
DOI: 10.3747/co.23.2711
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Rectal Adenocarcinoma and Splenic Marginal Zone Lymphoma

Abstract: Synchronous cancers of different primary origin are rare. Here, we describe the case of a patient with concomitant diagnoses of rectal adenocarcinoma and splenic marginal zone lymphoma (smzl).A 57-year-old woman initially presented with abdominal pain. Physical examination and computed tomography demonstrated massive splenomegaly, and a complete blood count revealed microcytic anemia and lymphopenia. During the subsequent evaluation, she presented with hematochezia, melena, and constipation, which prompted gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…1). [12–262] The data were extracted from the abstract in 34 articles, [17,37–39,64,75,76,78,81,94,97,103,129,134,151,162,166,170,174,176,192,195,212,221,222,229,232,234,251,252,256,260–262] of which 21 were in English, 5 in Japanese, 3 in Spanish, 2 in French, 2 in Chinese, and 1 in Czech.…”
Section: Resultsmentioning
confidence: 99%
“…1). [12–262] The data were extracted from the abstract in 34 articles, [17,37–39,64,75,76,78,81,94,97,103,129,134,151,162,166,170,174,176,192,195,212,221,222,229,232,234,251,252,256,260–262] of which 21 were in English, 5 in Japanese, 3 in Spanish, 2 in French, 2 in Chinese, and 1 in Czech.…”
Section: Resultsmentioning
confidence: 99%
“…The pathophysiology of MPMN remains poorly understood, but risk factors may include tobacco and alcohol intake, infections, immunosuppression, genetic predisposition, and toxic effects related to chemotherapy or radiotherapy treatments [ 16 ]. With regards to CRC and NHL, it has been suggested that lymphoma may be the initial event that suppresses the patient's defenses against the development of colorectal carcinoma [ [16] , [17] , [18] ]. On the other hand, Hirano et al [ 19 ] reported a patient with hereditary nonpolyposis colorectal cancer who developed NHL after curative resection of CRC.…”
Section: Discussionmentioning
confidence: 99%